Reabilitação pulmonar no Brasil: um inquérito nacional - Fernanda Nazareth Vitor Foureaux (2018)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a common, preventable and treatable disease characterized by persistent respiratory symptoms and chronic airflow obstruction, which represents a major health challenge and is a major cause of morbidity and mortality throughout the world. Pulmonary rehabilitation is considered by the literature as the most suitable non-pharmacological treatment for individuals with stable phase COPD. Some countries have been investing in pulmonary rehabilitation service (PRS) because of the strong evidence on the effectiveness of treatment in reducing costs to the sick population. In Brazil no studies have been identified that identify, quantify and characterize SRP, which is necessary to verify how frequent and how this form of treatment is offered to the population. Purpose: Identify, quantify and qualify the PRS in Brazil. Methods: This is a cross-sectional study, carried out through the form-response analysis, sent electronically to physiotherapists affiliated with Associação Brasileira de Fisioterapia Cardiorrespiratória e Fisioterapia em Terapia Intensiva (ASSOBRAFIR). The instrument used was a questionnaire developed by Alison et al., Which was translated into Portuguese and adapted to the Brazilian reality by the researchers of this study. The study used descriptive statistics with measures of central tendency and dispersion as well as percentages and frequency. Results: Between December 2017 and April 2018, 1,016 questionnaires were sent by e-mail to the physiotherapists associated with ASSOBRAFIR. Of this total, 94 questionnaires were answered, obtaining a response rate of 9.25%. Following the exclusion criterion, seven questionnaires were eliminated because they were duplicated and 34 were identified from sites that have a pulmonary rehabilitation service (SRP). SRP was identified in the five regions of the country with a higher concentration in the southeast (41%). The SRP are offered by multiprofessional team and the physiotherapists coordinate 25 SRP (73.5%). The programs are mostly performed two days a week (47.1%) and patients exercise for more than 40 minutes / session. The exercise program was cited as the main element of the program in 28 SRP (82.4%) and exercise prescription is most often done through the 6-minute walk test (6MWT). The evaluation is done in 86.4% of SRP and the reevaluation in 76.5%. The most cited barriers to implementation were inadequate financial resources (54.7%) and not part of the health department's management plan (33.9%). Conclusion: This study identified 34 PRS present in the five regions of Brazil. Most services are offered by private institutions, have a multidisciplinary team involved and are coordinated by physiotherapists. In general, they comply with the recommendations of international guidelines for pulmonary rehabilitation in relation to the procedures performed. The main barrier to implementation of the PRS identified in the country was the lack of financial investments.